2022
DOI: 10.1088/1755-1315/1057/1/012008
|View full text |Cite
|
Sign up to set email alerts
|

Survey on usage of single use plastic bags in Nepal

Abstract: The rapid urbanization and economic growth have caused increase of plastic products globally. The least developed countries (LDCs) have been facing severe problems with solid waste due to lack of people’s awareness, lack of skilled manpower to handle waste and necessary equipment to manage in sustainable manner. Nepal, a LDC in South Asia, lacks source segregation leading the maximum plastic items reaching to the landfill site. It is even difficult for the planning authorities to make effective plans for susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…In 2017, Ranjeeta Kakoti conducted a study in India that showed that dustbins and public garbage bins are the major methods of waste disposal, followed by dumping, which is consistent with our research [ 15 ]. In Nepal, a study conducted by Ashish Khanal in 2022 among the youth population concluded that 80.1% of the participants practiced waste segregation [ 16 ]. The reason for this could be the strict laws in Nepal and the promotion of waste segregation.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, Ranjeeta Kakoti conducted a study in India that showed that dustbins and public garbage bins are the major methods of waste disposal, followed by dumping, which is consistent with our research [ 15 ]. In Nepal, a study conducted by Ashish Khanal in 2022 among the youth population concluded that 80.1% of the participants practiced waste segregation [ 16 ]. The reason for this could be the strict laws in Nepal and the promotion of waste segregation.…”
Section: Discussionmentioning
confidence: 99%
“…Workplace waste management practices should be designed to reduce pollution and address climate change. Implementing recycling programs, composting biodegradable waste, reducing the use of disposable items, and encouraging employees to use reusable alternatives are effective waste management strategies that contribute to environmental sustainability (Khanal, 2022). The lack of proper separation at the source and an inefficient collection system in Nepal have resulted in a significant amount of waste ending up at the landfill site (Khanal et al, 2023).…”
Section: Strategies For Improving Occupational Health and Safetymentioning
confidence: 99%
“…Only 9% of these plastics are recycled (Prelims, 2022). The recycling of plastics includes process of sorting, cleaning, shredding, melting and remoulding of the materials (Khanal, 2022). The bioplastic prevents erosion, runoff, and vegetation establishment, which makes it an environmentally friendly method of waste disposal (Dili, 2022).…”
Section: Bioplasticsmentioning
confidence: 99%